Pancreatoblastoma Mimicking Liver Abscess: A Case Report - Syed, Z; Chakravarthy, S; Singh, M; Narayan, R (Nepalese Journal of Radiology, 2012)
Pancreatoblastoma is an extremely rare pancreatic tumour most commonly encountered in infants and young children. This is a case of childhood pancreatoblastoma being reported to emphasize the dilemma of clinical and radiological features in diagnosing this rare tumour. A 3-year-old boy complained of distension of the abdomen with mild jaundice. Initially, physical and radiological investigations were in favour of liver abscess. Histopathological examination of the resected specimen was interpreted as liver mass. Serological investigations and immunohistochemistry for malignancy were helpful in suspecting Pancreatoblastoma. Pancreatoblastoma can mimic a liver mass (caudate lobe) on imaging as is shown in this case report. DOI: http://dx.doi.org/10.3126/njr.v1i1.6321 Nepalese Journal of Radiology Vol.1(1): 33-36